The marginal socialization among the servants: some examples in the novel el "Guzmán de Alfarache" (1599-1604) - Rodríguez Giles, Ana Inés (Cuadernos de Historia Moderna, 2013)
During the early modern ages poor people who couldn’t enter into the labor market were forced to work. Some of them were inserted in service occupations, which were not always economically productive, but they were used to reproduce their masters’ status. Our study aims to analyze some examples on this phenomenon in el Guzmán de Alfarache (1599-1604). This novel –which as literary text serves to observe a social reality–, shows the ways of socialization that existed bewteen the mozos in the domestic space, where they reproduced marginal behaviours in a ‘non marginal’ socialization environment that was imposed on them.